Belatacept after kidney transplantation in adolescents: a retrospective study. (5th March 2017) - Lerch, Christian; Kanzelmeyer, Nele K.; Ahlenstiel‐Grunow, Thurid; Froede, Kerstin; Kreuzer, Martin; Drube, Jens; Verboom, Murielle; Pape, Lars
Summary: Regardless of recipient age at kidney transplantation (KTx), patients are at greatest risk for graft loss in adolescence, partly due to nonadherence to an oral immunosuppressive regimen. Belatacept, a non‐nephrotoxic, first‐in‐class immunosuppressant that inhibits costimulation of T cells requires intravenous application only every 4 weeks, potentially leading to better adherence. However, it is only approved for use in adults. We report here the findings of the first study of belatacept in adolescents, comprising all patients in our department switched to belatacept post‐KTx. Six patients (median age 15.5 years) were switched after a median of 7.5 months (range 23 days to 12 years), treatment range 3–28 months (cumulative 83 months): Three patients switched early (<3 months after KTx) had increased estimated glomerular filtration rate (GFR); one patient switched 12 years post‐KTx has stable GFR; two patients were switched following rapid decline of and with markedly impaired GFR, changing slope in one patient. One patient had one acute rejection. In addition of two patients who received belatacept for other conditions, the only relevant adverse event was neutropenia (after a cumulative 109 months). Belatacept as primary immunosuppression is an option in Epstein–Barr virus‐seropositive nonadherent adolescents if administered sufficiently early before deterioration of graft function.